Vegetation and soil seed bank relationships across microhabitats in an abandoned Quercus suber parkland under simulated fire - Torres, Ivan; Urbieta, Itziar R; Moreno, Jose M (Ecoscience, 2012)
Mediterranean agro-forestry systems are undergoing rapid change due to abandonment. This turns formerly cultivated or grazed oak-tree parklands (i.e., savanna-type formations called “dehesas”) into flammable formations of scattered trees within a matrix of shrubs with open spaces. Wildfires can now occur, threatening the persistence of these formations. Fire-prone shrublands commonly regenerate after fire from seeds stored in the soil. Understanding the relationships between standing vegetation and the soil seed bank across microhabitats can help predict the response of the system in case of fire. Here we investigated these relationships in an abandoned Quercus suber (cork oak) dehesa in central Spain. Vegetation and soil were sampled and assigned to different microhabitats: under the trees (TRC), in dense shrub cover (DSC), and in low shrub cover (LSC). A heat shock was applied to half of each sample to simulate fire; the other half served as control. Both sets of samples were then germinated in a greenhouse. Almost 90% of the species were herbs, while the rest were woody shrubs. The number of species recorded in TRC and DSC was lower than in LSC, in which species richness, particularly herbs, was maximal. Heating increased the total number of species that germinated, but mean species richness per sample was not altered. Heating markedly increased the number of germinations in all microhabitats, particularly those of woody species. Furthermore, the germination of shrubby species increased in the 3 microhabitats, notably in TRC. While the standing plant community was well differentiated among microhabitats, this was not the case for the soil seed bank, which was homogeneous across microhabitats, with or without heating. We conclude that the high density of shrubby seeds found in TRC or in the other microhabitats presents substantial threats to the persistence of Q. suber parklands in case of fire.
Keywords: cistus; Cork oak; Dehesa; Encroachment; Erica; Mediterranean shrublands

Long-time variations in leaf mass and area of Mediterranean evergreen broad-leaf and narrow-leaf maquis species - Gratani, L; Varone, L (Photosynthetica, 2006)
Morphological (dry mass, DM; surface area, LA; leaf mass per area, LMA), anatomical (leaf thickness, L), phenological (leaf life span, LL), and physiological (net photosynthetic rate, PN) leaf traits of the evergreen species co-occurring in the Mediterranean maquis developing at Castelporziano (Rome) were tested. The correlation analysis indicated that LMA variation was tightly associated with LL variations: Cistus incanus and Arbutus unedo had a short LL (4±1, summer leaves, and 11±1 months, respectively) and low LMA (153±19 g m –2 ) values, Quercus ilex, Phillyrea latifolia, and Pistacia lentiscus high LMA (204±7 g m –2 ) and long LL (22±3 months), Erica arborea, Erica multiflora, and Rosmarinus officinalis a short LL (9±2 months) and an either high (213±29 g m –2 , R. officinalis and E. multiflora) or low (115±17 g m –2 , E. arborea) LMA. LMA values were significantly (p≤0.05) correlated with PN (r≥0.68). In the tested species, LMA increased in response to the decrease of the total rainfall during the leaf expansion period. LMA variation was due to the unequal variation of DM and LA in the considered species. LMA is thus a good indicator of evergreen maquis species capability to respond to climate change, in particular to total rainfall decrease in the Mediterranean basin.
Keywords: dry mass; Erica; leaf life span; Leaf mass per area; Phillyrea; Pistacia; Quercus; RAINFALL; Rosmarinus.

Adaptive photosynthetic strategies of the Mediterranean maquis species according to their origin - Gratani, L; Varone, L (Photosynthetica, 2004)
In consideration of their origin the adaptive strategies of the evergreen species of the Mediterranean maquis were analysed. Rosmarinus officinalis L., Erica arborea L., and Erica multiflora L. had the lowest net photosynthetic rate (PN) in the favourable period [7.8±0.6 µmol(CO2) m -2 s -1 , mean value], the highest PN decrease (on an average 86 % of the maximum) but the highest recovery capacity (>70 % of the maximum) at the first rainfall in September. Cistus incanus L. and Arbutus unedo L. had the highest PN during the favourable period [15.5±5.2 µmol(CO2) m -2 s -1 , mean value], 79 % decrease during drought, and a lower recovery capacity (on an average 54 %). Quercus ilex L., Phillyrea latifolia L., and Pistacia lentiscus L. had an intermediate PN in the favourable period [9.2±1.3 µmol(CO2) m -2 s -1 , mean value], a lower reduction during drought (on an average 63 %), and a range from 62 % (Q. ilex and P. latifolia) to 39 % (P. lentiscus) of recovery capacity. The Mediterranean species had higher decrease in PN and stomatal conductance during drought and a higher recovery capacity than the pre-Mediterranean species. Among the pre-Mediterranean species, P. latifolia had the best adaptation to long drought periods also by its higher leaf mass per area (LMA) which lowered leaf temperature thus decreasing transpiration rate during drought. Moreover, its leaf longevity determined a more stable leaf biomass during the year. Among the Mediteranean species, R. officinalis was the best adapted species to short drought periods by its ability to rapidly recover. Nevertheless, R. officinalis had the lowest tolerance to high temperatures by its PN dropping below half its maximum value when leaf temperature was over 33.6 °C. R. officinalis may be used as a bioindicator species of global change.
Keywords: arbutus; cistus; drought period; Erica; Phillyrea; Pistacia; Quercus; recovery capacity; Rosmarinus; Stomatal conductance